Career Competencies for Academic Career Progression: Experiences of Academics at a South African University - Barnes, Nina; du Plessis, Marieta; Frantz, José (Frontiers in Education, 2022)
An understanding of career competencies is critical for the progression of academic careers, as it influences the availability of adequate and capable academic staff at all levels within universities. The study aimed to explore and describe the career competencies that academics demonstrate to successfully progress in their careers, while theoretically underpinned by an integrated competency framework. This report is based on the qualitative experiences, gathered through semi-structured interviews of eight academic staff in various career phases, in a South African university. Data was thematically analysed, while a deductive modality was adopted to identify the competencies. The findings align very closely with the dimensions of the integrated competency framework, including reflective competencies: gap analysis, self-evaluation, social comparison, and goal orientation; communicative competencies: information seeking and negotiation; and behavioural competencies: strategy alignment, control and agency, university awareness, continuous learning and collaboration. Whilst the study did not include a comparative analysis, it is interesting to note that strategy alignment was the most commonly found competency, with negotiation only demonstrated by more senior academics. A career competency approach provides leaders and development practitioners in the higher education sector with factors to consider, as they attempt to understand holistic development for academic career progression. Moreover, how to assist and support the development of academic career progression. It offers academics a keen awareness, as a personal resource, to engage and navigate self-directed career management behaviour.